NTM beyond the lungs: a case series of non-tuberculous mycobacterial infection at extrapulmonary sites - Khanduri, Rakhee; Vashishht, Megha; Sethi, Vikram; Shahnwaz; Kotwal, Aarti (International Journal of Research in Medical Sciences, 2025)
Background: In this case series, the results of documented non-tuberculous mycobacteria (NTM) infections, which have emerged as important pathogens, mainly among individuals with immunocompromised status have been studied. The report showcases the clinical presentation, diagnostic modality, treatment as well as outcome and results regarding the 8 patients who were diagnosed with NTM infection at extrapulmonary locations via molecular techniques. Methods: It involves retrospective analysis of patients who were diagnosed with NTM infection at the Himalayan Institute of Medical Sciences, Swami Rama Himalayan University, in the last 2 years, who were diagnosed using molecular tests. The specific details of clinical presentation, diagnostic methods and treatment regimens, along with outcomes, were reviewed retrospectively and summarized. Results: The outcomes comprised 8 patients (5 females and 3 males) between 19 and 79 years. The signs and varied symptoms included fever, headache, cough and weakness. The confirmatory diagnosis was followed by Polymerase chain reaction (PCR) for NTM, biopsy from the site, such as abdominal and vertebrae and pleural fluid analysis. Most patients showed significant clinical improvement after the diagnosis and appropriate treatment. Conclusions: This case series highlights the diverse clinical manifestations of NTM infections at extrapulmonary sites, emphasizing the importance of early diagnosis and appropriate management. Clinicians should maintain a high index of suspicion for NTM infections, especially in atypical presentations and immunocompromised patients.